Α dual‐hop equivalent structure of a generalised multi‐hop free‐space optics network. Issue 5 (29th January 2021) - Androutsos, Nikolaos A.; Nistazakis, Hector E.; Sandalidis, Harilaos G.; Leitgeb, Erich; Tombras, George S.
Abstract: The performance of free‐space optics links strongly depends on scintillation effects caused by the atmospheric turbulence appearance. A widely adopted way to counterbalance the expected deterioration due to scintillation is to employ cooperative and multi‐hop arrangements. However, the use of multiple relays increases significantly the complexity of the mathematical models used to describe the overall performance of the system. Taking the latter into account, we approximate a generic multiple relay‐assisted free‐space optical configuration with a dual‐hop link in order to simplify the performance analysis. To this end, we provide new mathematical derivations for the evaluation of the outage probability and the average bit error rate by assuming typical turbulence models.